Conducive environments reduce sleep disturbances and improve sleep quality: a quality improvement project. Issue 1 (5th March 2021) - Ho, Alexander G.T.; Tan, Mary; Perez, Hilario M.; Tan, Ching Nee.; Mordiffi, Siti Z.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Aim: The current implementation project aimed to improve patients' sleep quality in a hospital by implementing targeted interventions to reduce sleep disturbances. Methods: The Silent Night project was implemented in two general units of an academic tertiary hospital. The project comprised three phases: preimplementation, implementation, and postimplementation. Patient surveys were administered to obtain patients' perspectives on the sources of noise disturbances at night. Noise-monitoring machines were installed in two wards to obtain objective data on noise levels at night. Concurrently, data were collected on noise-generating activities that were observed. Results: The overall quality of sleep reported by patients improved by 17% (from 73.5 to 88.9%). Patients' survey reported reduced noise disturbances from direct care activities, environmental noise and medical equipment alarms. The mean noise level in the orthopedics unit reduced significantly from 57.04 to 55.22 dB with a corresponding decrease in noise generating activities by 60% (from 362 to 144). In the geriatric unit, the mean noise level increased from 51.36 to 53.12 dB but is within the National Environmental Agency's permissible noise level of 55 dB even though the noise generating activities reduced significantly by 92.2% (from 954 to 74). Conclusion: The 'Silent Night' project has successfully reduced noise disturbances generating from environment and nursing care activities and improved patients' sleep quality in the hospital. Sharing sessions regarding sources of noise and the 'Silent Night' poster promoted the awareness of noise disturbances in healthcare professionals, visitors, and patients.